2012
DOI: 10.1097/dcr.0b013e31826fea6a
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Mesorectal Extension Has Prognostic Significance in Patients With T3 Rectal Cancer

Abstract: Depth of mesorectal extension >5 mm is a significant prognostic factor in patients with T3 rectal cancer. Depth of mesorectal extension especially may be more important than the nodal status in predicting the oncologic outcome for patients who had received preoperative chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 18 publications
2
48
1
5
Order By: Relevance
“…Many other studies analyzed the impact of extramural spread (< 5 mm and > 5 mm) with respect to the survival rate in patients with no neoadjuvant chemo therapy or preoperative radiotherapy (6,10). Other studies have also analyzed the impact of extramural spread with respect to the survival rate in patients with neoadjuvant chemotherapy and preoperative radiotherapy (8,25). These studies support the fact, patients with DME > 5 mm have worse prognosis compared with DME < 5 mm.…”
Section: Re-categorization Of T3 Sub-stagingsupporting
confidence: 48%
See 2 more Smart Citations
“…Many other studies analyzed the impact of extramural spread (< 5 mm and > 5 mm) with respect to the survival rate in patients with no neoadjuvant chemo therapy or preoperative radiotherapy (6,10). Other studies have also analyzed the impact of extramural spread with respect to the survival rate in patients with neoadjuvant chemotherapy and preoperative radiotherapy (8,25). These studies support the fact, patients with DME > 5 mm have worse prognosis compared with DME < 5 mm.…”
Section: Re-categorization Of T3 Sub-stagingsupporting
confidence: 48%
“…In a study of 679 patients with rectal cancer, MERCURY group substantiated DME to be equivalent on MRI and histopathology with a mean difference of less than 0.5 mm (11), it shows that MRI evaluation is almost as accurate as histopathology examination. A study performed by Shin et al found no significant difference between T3a and T3b or T3c and T3d with respect to the 5-year survival rate but when re-categorized as T3ab (DME < 5 mm) and T3cd (DME < 5 mm), the 5-year survival rate for T3ab was significantly higher than T3cd (8).…”
Section: Re-categorization Of T3 Sub-stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Yavuz Ozdemir*, Mehmet Levhi Akin, Ilker Sucullu, Ahmet Ziya Balta, Ergun Yucel course and clinical outcome in colorectal cancer patients are influenced by not only oncological characteristics of the tumor itself but also host response factors (Shin et al, 2012;Li et al, 2013). Many biomarkers have been studied as supplementary tools for further classification of the patients into the subgroups based on the current TNM staging system.…”
Section: Pretreatment Neutrophil/lymphocyte Ratio As a Prognostic Aidmentioning
confidence: 99%
“…Con respecto a la linfadenectomía, se considera que la misma debe incluir un mínimo de 12 ganglios para una correcta estadificación, ya que en algunos estudios ha demostrado mejorar la sobrevida total con independencia de la presencia o ausencia de metástasis a nivel de los mismos (13) . Sin embargo, el ensayo clínico COST de la Clínica Mayo no encuentra una correlación entre el número de ganglios resecados y la sobrevida (14) , por lo que el debate acerca del número mínimo aceptable de ganglios permanece hasta el día de hoy.…”
Section: Discussionunclassified